Untersuchungen zu kontinuums- und bruchmechanischen Methoden für die Prognose des Crashverhaltens toleranzbehafteter Strukturklebverbindungen - Bobbert, Mathias

Paying for Performance in Private Equity: Evidence from Venture Capital Partnerships - Hüther, Niklas; Robinson, David T.; Sievers, Sönke; Hartmann-Wendels, Thomas (Management Science (VHB-JOURQUAL 3 Ranking A+))
We offer the first empirical analysis connecting the timing of general partner (GP) compensation to private equity fund performance. Using detailed information on limited partnership agreements between private equity limited and general partners, we find that “GP-friendly” contracts—agreements that pay general partners on a deal-by-deal basis instead of withholding carried interest until a benchmark return has been earned—are associated with higher returns, both gross and net of fees. This is robust to measures of performance persistence, time period effects, and other contract terms and is related to exit-timing incentives. Timing practices balance GP incentives against limited partner downside protection.
Keywords: venture capital; compensation; private equity; VC partnership; pay-performance relation

ELOBEV - Erforschung von elektrolytischen Beschichtungssystemen für Verbindungselemente aus höchstfesten Werkstoffen - Bangel, Martin; Neubauer, Michael; Kuhlmann, Matthias; Rossel, Moritz Sebastian; Klostermann, Heidrun; Rablbauer, Ralf; Weber, Marius (Projektband der BMBF-Förderinitiative Innovative Elektrochemie mit neuen Materialien – InnoEMat)

Coaching on the Job bei Unternehmen des Maschinen- und Anlagenbaus - Wissenslücken schließen zur Weiterpflege modernisierter IT-Anwendungen - Fazal-Baqaie, Masud; Strüwer, Jan-Niclas; Schmelter, David; Dziwok, Stefan (Projektmanagement und Vorgehensmodelle 2019 (PVM 2019))

Improvement of Software Requirements Quality based on Systems Engineering - Holtmann, Jörg

Component-Based Refinement and Verification of Information-Flow Security Policies for Cyber-Physical Microservice Architectures - Gerking, Christopher; Schubert, David (International Conference on Software Architecture (ICSA 2019))

Application-aware Intrusion Detection: A Systematic Literature Review and Implications for Automotive Systems - Schubert, David; Eikerling, Hendrik; Holtmann, Jörg (17th escar Europe : embedded security in cars)

Monitoring and Control of Production Processes based on Key Performance Indicators for Mechatronic Systems - Wohlers, Benedict; Dziwok, Stefan; Pasic, Faruk; Lipsmeier, Andre; Becker, Matthias (International Journal of Production Economics)
The processes for manufacturing and operating modern technical products require expertise in multiple disciplines like mechanical engineer-ing, electrical engineering, and software engineering. Assessing the current condition and quality of these processes and the machines in-volved is challenging due to the inherent complexity of the products and the required expertise in multiple engineering domains. Globaliza-tion and increasing competition make it necessary to reduce production costs while at the same time ensuring high throughput and product quality. Without the ability to precisely assess the condition and quality of production processes and involved machines, taking action to steer these metrics is nearly impossible and results in unnecessary high production costs. In our previous publications, we introduced the concept of Key Performance Indicators (KPIs) for mechatronic systems as a concept to assess the condition and quality of products and production processes in a graspable yet substantial and efficient way. In this paper, we further refine our KPI concepts und evaluate them for two different use cases: we apply our KPI concept to a manufacturing process in the mechatronic system domain and an operation process in the food production domain. We provide detailed insights in how we applied our concepts within these domains and report about lessons learned. In addition, we provide a business case estimation for our soft-ware solution that assesses the KPIs of our food production domain example.

Inverse optimal control problem: the linear-quadratic case - Jean, Frederic; Maslovskaya, Sofya (2018 IEEE Conference on Decision and Control (CDC))

On projective and affine equivalence of sub-Riemannian metrics - Jean, Frédéric; Maslovskaya, Sofya; Zelenko, Igor (Geometriae Dedicata)